The behavioural and neuropathologic sexual dimorphism and absence of MIP-3α in tau P301S mouse model of Alzheimer’s disease - Sun, Yao (J Neuroinflammation, 2020)
BACKGROUND: Tau hyper-phosphorylation has been considered a major contributor to neurodegeneration in Alzheimer’s disease (AD) and related tauopathies, and has gained prominence in therapeutic development for AD. To elucidate the pathogenic mechanisms underlying AD and evaluate therapeutic approaches targeting tau, numerous transgenic mouse models that recapitulate critical AD-like pathology have been developed. Tau P301S transgenic mice is one of the most widely used mouse models in AD research. Extensive studies have demonstrated that sex significantly influences AD pathology, behavioral status, and therapeutic outcomes, suggesting that studies using mouse models of AD must consider sex- and age-related differences in neuropathology, behavior, and plasma content. METHOD: We systematically investigated differences in tau P301S transgenic mice (PS19 line) and wildtype littermates of different sex behavioral performance, tau neuropathology, and biomarkers in plasma and brain. RESULTS: Male P301S transgenic mice exhibited significant changes in weight loss, survival rate, clasping, kyphosis, composite phenotype assessment, nest building performance, tau phosphorylation at Ser202/Thr205, and astrocyte activation compared to that of wild-type littermates. In contrast, female P301S transgenic mice were only sensitive in the Morris water maze and open field test. In addition, we characterized the absence of macrophage-inflammatory protein (MIP-3α) and the upregulation of interferon (IFN)-γ, interleukin (IL)-5, and IL-6 in the plasma of P301S transgenic mice, which can be served as potential plasma biomarkers in P301S Tg mice. Male P301S transgenic mice expressed more monokine induced by IFN-γ (MIG), tumor necrosis factor-α (TNF-α), IL-10, and IL-13 than those of female P301S mice. CONCLUSION: Our findings highlight sexual dimorphism in the behavior, neuropathology, and plasma proteins in tau P301S transgenic AD mice, indicating that the use of male P301S transgenic mice may be more suitable for assessing anti-phosphorylated tau therapeutic strategies for AD and related tauopathies, and the MIP-3α may be a new potential plasma biomarker.